Horizontal collaboration in logistics: A feasible task for group purchasing - Ghaderi, Hadi; Avakh Darestani, Soroush; Zulkiffle, Leman; Mohd Yusof, Ismail (Inderscience Enterprises Ltd., 2012)
Current attention to the argument of collaborative procurement has been investigated by both academia and industry practitioners as the concept of group purchasing. This paper first reviews the literature on horizontal collaboration in purchasing task and recognises the interface between purchasing progress and the logistical point of view of supply as the accomplishing task of the procurement cycle. Secondly, it examines the effects of a successful horizontal collaboration in logistics activities among a group of small and medium sized food enterprises (SMEs) which have participated in a purchasing consortium. ‘Homo-regional firms’ are introduced as a logistics concept illustrating the potentiality in establishing horizontal collaboration in logistics activities in order to gain a competitive advantage. Methodology consists of data collection through quantitative questionnaires in direct contact with the firms. The results show a reduction of 10% to 30% in outbound logistics cost in comparison to the time period in which the firms were undergoing procurement by themselves.